Analisis Kemampuan Berpikir Kreatif Matematis Siswa Pada Materi Segitiga - Indriany A Kadir; Tedy Machmud; Kartin Usman; Nancy Katili (Jambura Journal of Mathematics Education, 2022)
This study aims to describe the mathematical creative thinking skills of SMP Negeri 1 Dungaliyo students on triangle material using descriptive methods. The subjects of this study were the seventh-grade students of SMP Negeri 1 Dungaliyo in the odd semester of the 2020/2021 academic year, as many as 27 students. The instrument used in this study was a test to obtain data on mathematical creative thinking skills and interviews to complement and strengthen the information derived from giving tests on triangle material that had been empirically validated. To see students' mathematical creative thinking skills, 4 indicators are used, namely 1). Smoothness (fluency); 2) Dexterity (flexibility); 3). Authenticity (authenticity); 4). Details (description). The data analysis technique used in this research is percentage analysis. Based on the data obtained for indicators of skill (fluency) of 50.93%, flexibility (flexibility) of 46.14%, originality of 33.33%, and details (elaboration).